Developing effective partnerships in reporting student achievement : making links between educative theory and schools reporting practices : a thesis presented as partial fulfilment of the requirements for the degree of Master of Educational Administration, Massey University, Albany - Taylor, Kerry (Massey University, 2003)
This thesis examines how three participant schools reported the achievement of students to parents and the extent to which reporting practices reflected current educative theories and effective partnership. The understanding of parents and teachers of the process of the reporting practices, and how practice promoted or hindered educative partnerships between teachers and parents were examined. Over the past ten years schools, in New Zealand, have spent much time realigning their reporting practices to New Zealand national requirements, and the expectations of their school communities. This research examined what led schools to make their decisions about their reporting practices, comments on the effectiveness of current practices and draws conclusions based on the findings of the research. Evaluative case study was selected as the methodology for this study. The study is located within three school contexts and involves in-depth examination and analysis of teachers' and parents' perceptions about educative theory, partnership and reporting student achievement. The methodology used provided an opportunity to evaluate current practice, provide feedback to each participant school and allowed the cooperative development of recommendations for improving reporting processes. Issues and themes were identified as data were gathered. Exploration of emerging themes occurred throughout the data gathering phase. Data gathering strategies included parent and teacher questionnaires, individual interviews with senior leaders, teachers and parents and document analysis. That data revealed a number of themes in relation to educative theory, reporting and partnership. Initial themes included: important educational outcomes identified by parents and teachers, the purpose of reporting identified by parents and teachers, the type of information parents found helpful, the role of teacher-parent interviews, the desire of parents to be actively involved in their children's' learning, and the frequency and timing of personal contact between parents and teachers. This thesis concludes that each school had not directly linked their practices to educative theory or conditions for effective partnerships with parents. A key purpose identified by both parents and teachers was the support of parents in helping their children achieve, yet this key purpose was omitted from any documentation identifying purposes and, in many cases, from the implementation of reporting processes by teachers. A further conclusion is that the link between educative theories, the relationship of those theories to the reporting process and how effective links could be made to develop effective partnerships between teachers, parents and students is a significant area for future research.
Keywords: Grading and marking (Students)